Customer Billing System for Excavator Workshop - YAU, JIA YIN; Nureize Arbaiy (Applied Information Technology And Computer Science, 2025)
In contemporary business operations, efficient management of invoices is critical to track sales, expenses, and cash flow. Because of the inefficiencies and error-prone manual processes using notebooks and Excel, there is a demand for a more effective invoice preparation and management system. This study introduces a web billing system that integrates customer management and billing administration, enabling simplified invoicing, streamlined payment tracking, and effective customer account management. Leveraging this system facilitates easy monitoring of transaction history, invoice generation, and comprehensive customer information handling. The web-based approach ensures seamless accessibility and scalability, contributing to improved financial management, heightened customer satisfaction, and increased operational efficiency. Future research may explore additional functionalities and user feedback for continuous enhancement of the system.